2016
DOI: 10.1111/papr.12524
|View full text |Cite
|
Sign up to set email alerts
|

Translation and Validation of the Thai Version of a Modified Brief Pain Inventory: A Concise Instrument for Pain Assessment in Postoperative Cardiac Surgery

Abstract: The BPI-T is a concise instrument for pain assessment in postoperative cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 32 publications
0
30
0
Order By: Relevance
“…The BPI was initially developed to evaluate pain in patients with malignancy, however, it has since been validated and used to evaluate chronic pain of other aetiologies and also for acute pain in the postsurgical population. [18][19][20] In the absence of any 'gold-standard' tool for the assessment of pain in survivors of critical illness, the BPI was selected for use as it is frequently employed to assess pain in this population. 21 It also received positive feedback from patient and public involvement when it was piloted in a previous study conducted by this research group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BPI was initially developed to evaluate pain in patients with malignancy, however, it has since been validated and used to evaluate chronic pain of other aetiologies and also for acute pain in the postsurgical population. [18][19][20] In the absence of any 'gold-standard' tool for the assessment of pain in survivors of critical illness, the BPI was selected for use as it is frequently employed to assess pain in this population. 21 It also received positive feedback from patient and public involvement when it was piloted in a previous study conducted by this research group.…”
Section: Discussionmentioning
confidence: 99%
“…The format of the questions is a combination of free text, shading affected areas on a diagram and numeric rating scales from 0 to 10, where 0 represents no pain and 10 represents worst pain. The BPI was initially developed to evaluate pain in patients with malignancy, however, it has since been validated and used to evaluate chronic pain of other aetiologies and also for acute pain in the postsurgical population 18–20…”
Section: Methodsmentioning
confidence: 99%
“…Thai-BPI. The Thai-BP questionnaire is an assessment tool for assessing the pain and physical condition of patients 12 , which can re ect the pain of patients for a period of time. It can assess the intensity of pain in patients with the most severe pain, the slightest pain, and general pain.…”
Section: Methodsmentioning
confidence: 99%
“…It was also translated and validated in different cultures and disease settings. In a recent study conducted on Thai cardiac patients, Keawnantawat et al [50] reported that the BPI-T also has good internal consistency (Cronbach's alpha coefficients 0.76 and 0.85) [50]. Pearson's correlation coefficients at 0.35 to 0.70 supported the convergent validity to the NRS.…”
Section: Non-verbal Scale Faces Pain Scale -Revised (Fps-r)mentioning
confidence: 95%